Scrappy - Molarsky, Osmond (New York : Dodd, Mead, 1983)
After her talents are grudgingly recognized and she is accepted as the only girl member of Joe's Garage soccer team, eleven-year-old Scrappy feels let down when the sponsorship changes and the feminine owner of a dress shop becomes the new coach.
Keywords: Soccer stories; Sports stories; Soccer -- Fiction